ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH PADA PT. BANK PEMBANGUNAN DAERAH KALIMANTAN TENGAH KANTOR CABANG PANGKALAN BUN - Alvin Adam Fauzie; Nur Widiastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
This research aims to identify the influence of service quality on customer loyalty at PT. Bank Pembangunan Daerah Kalteng, Pangkalan Bun Branch Office. The research method used is quantitative, which describes the relationship and impact of service quality variables and their dimensions on customer loyalty. According to Tjiptono (2000), one of the factors that affect customer loyalty is service quality and banking products. Service quality is formed by five dimensions: assurance, reliability, tangibility, empathy, and responsiveness. This research was conducted by distributing an online questionnaire in the form of a Google Form to 100 customers of PT. Bank Pembangunan Daerah Kalteng, Pangkalan Bun Branch Office, preceded by mini interviews with several customers regarding service-related issues. The research concludes that the service quality variable X, through its forming dimensions of assurance, reliability, tangibility, empathy, and responsiveness, has a simultaneous influence on the customer loyalty variable Y, with an R2 value of 0.399 or 33.9%. However, none of the five dimensions of the service quality variable X have a partial influence on the customer loyalty variable Y. This research also found that there are several aspects of service quality at PT. Bank Pembangunan Daerah Kalteng, Pangkalan Bun Branch Office that are highlighted by customers, especially in the tangibility dimension, which still receives low scores from the responses of 100 customer questionnaires.